A review on efficiently integrated passive distillation systems for active solar steam evaporation. (March 2022) - Arunkumar, T.; Lim, Hyeong Woo; Lee, Sang Joon
Abstract : Solar energy-driven desalination is one of sustainable means to produce reusable water. Recently, solar distiller formally known as a solar still (SS) has been commonly employed to get freshwater through evaporation and consequent condensation process. However, such passive systems are typically slow on the distillation process, because bulk heating requirement and other energy losses. To increase the fresh water productivity of the passive distillation systems, researchers have usually adopted concentrators, reflecting mirrors, evacuated tube collectors (ETC), energy absorbing-engineered nanoparticles and energy storage (sensible and latent heat) materials. In this manner, water in a distiller can obtain additional heat and speedy evaporation take place immediately. Thus, efficient integration of passive distillation is highly useful to achieve appreciable production rate of fresh water for human daily needs. In this aspect, many researchers continuously tried to develop new innovative technologies for effective solar desalination. The main objective of this assessment is to review the current integration strategies and consequences for improving the productivity of solar distillers. Here, the term integration comprises additional heat sources, including heat confinement to broadband nanoparticles (micro-integration), concentrators, reflecting-mirrors (macro-integration), latent heat storage (LHS), sensible heat storage (SHS), and wicking cloth-based absorbers. This review exclusively focused on the newest results in the year of 2020–2021. In addition, the challenges, limitations, and requirements for future prospects are discussed. Highlights: Effective integration of solar still is essential to produce adequate fresh water. Integration of concentrator-coupled solar distillation systems are examined. The gear-up trends in photothermal and energy storage materials are analyzed. Recycling of latent heat in the multi-effect distillation technique is discussed. Effective integration enhances the evaporation rate of solar desalination systems.